Pricing Internet Traffic: Exclusion, Signalling and Screening - Bruno Jullien; Wilfried Sand-Zantman (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider a network that intermediates traffic between free content providers and consumers. While consumers do not know the traffic cost when deciding on consumption, a content provider knows his cost but may not control the consumption. We study how pricing consumers' and content providers' sides allows both profit extraction from the network and efficient information transmission. In the case of uniform tariff, we argue that a positive price-cap on the charge to content is optimal (with no constrain on the consumer side). Proposing menus helps signaling useful information to consumers and therefore adjusting consumption to traffic cost. In the case of menus, we show that optimal mechanisms consist in letting the content producers choose between different categories associated with different prices for content and consumers. Our results are robust to competition between ISPs and to competition between contents. We also show that when (competitive) content providers choose at small cost between a pay and a free business model, a price-cap at cost on the price for content improves efficiency.
Keywords: D00; 330